The efficacy of stereotactic radiotherapy followed by bevacizumab and temozolomide in the treatment of recurrent glioblastoma: a case report - Zhong, Wangyan; Mao, Jiwei; Wu, Dongping; Peng, Jianghua; Ye, Wanli (Frontiers in Pharmacology, 2024)
Glioblastoma (GBM) is the most common and aggressive malignant brain tumor among adults. Despite advancements in multimodality therapy for GBM, the overall prognosis remains poor, with an extremely high risk of recurrence. Currently, there is no established consensus on the optimal treatment option for recurrent GBM, which may include reoperation, reirradiation, chemotherapy, or a combination of the above. Bevacizumab is considered a first-line treatment option for recurrent GBM, as is temozolomide. However, in recurrent GBM, it is necessary to balance the risks and benefits of reirradiation in combination with bevacizumab and temozolomide. Herein, we report the case of a patient with recurrent GBM after standard treatment who benefited from stereotactic radiotherapy followed by bevacizumab and temozolomide maintenance therapy. Following 16 months of concurrent chemoradiotherapy (CCRT), the patient was diagnosed with recurrent GBM by a 3-T contrast-enhanced magnetic resonance imaging (MRI). The addition of localized radiotherapy to the ongoing treatment regimen of bevacizumab, in combination with temozolomide therapy, prolonged the patient’s disease-free survival to over two years, achieving a significant long-term outcome, with no notable adverse effects observed. This clinical case may provide a promising new option for patients with recurrent GBM.